Investment And Sustainable Development Of The Fisheries Sector In Algeria In The Absence Of Pluridisciplinary Approaches: Results Of A Prospective - Salah Eddine, Guedri; Saïd Chaouki, Chakour (Université de M'sila, 2016)
This article tries, to demonstrate the relationship between investment and sustainable development of the sector of fisheries in Algeria. Our research defends the thesis: "Unlike the industrial sector, the development of the fisheries sector and the efficiency of fishing units are not necessarily proportional to the level of investment in the sector." This article also tries to highlight the interest of both qualitative, quantitative, and pluridisciplinary studies and their contribution to good governance in the sector.
Keywords: Fishing, Sustainable Development, Investment, Prospective Approach, Pluridisciplinary Approaches, Algeria.